Pleomorphic colonies of Clostridium perfringens isolated from intestinal content from healthy goats - Mignaqui, Ana Clara (2021)
Clostridium perfringens is a ubiquitous worldwide distributed bacterium. It can be isolate from soil, water, gastrointestinal tract of healthy animals and humans, and from clinical specimens. Under certain circumstances it can produce a variety of diseases in goats and sheep such as enterotoxaemia and hemorrhagic enteritis due to the effect of different toxins that this bacterium can produce. The pleomorphic characteristics of C. perfringens colonies have already been described.